Between surveillance and recognition: Rethinking digital identity in aid. Issue 1 (April 2021) - Weitzberg, Keren; Cheesman, Margie; Martin, Aaron; Schoemaker, Emrys
Identification technologies like biometrics have long been associated with securitisation, coercion and surveillance but have also, in recent years, become constitutive of a politics of empowerment, particularly in contexts of international aid. Aid organisations tend to see digital identification technologies as tools of recognition and inclusion rather than oppressive forms of monitoring, tracking and top-down control. In addition, practices that many critical scholars describe as aiding surveillance are often experienced differently by humanitarian subjects. This commentary examines the fraught questions this raises for scholars of international aid, surveillance studies and critical data studies. We put forward a research agenda that tackles head-on how critical theories of data and society can better account for the ambivalent dynamics of 'power over' and 'power to' that digital aid interventions instantiate.